Swimming with the Plesiosaur - Stone, Rex.; Spoor, Mike. (New York : Scholastic Inc., 2009)
"Tom and Jamie can't believe their luck when they find a secret entrance to a prehistoric world filled with dinosaurs. Loaded with snorkeling gear, the boys decide to explore the cove itself. But there are some not-so- friendly creatures lurking, including a hungry plesiosaur that wants a snack! Can the boys save their dinosaur friends--and themselves--from the deadliest creature in the prehistoric ocean?"--p.[4] of cover.
RL3.
007-010.
Accelerated Reader AR
Keywords: Dinosaurs -- Juvenile fiction; Plesiosauria -- Juvenile fiction